Inteligencia emocional y clima laboral en colaboradores de una empresa comercializadora de productos cerámicos en la ciudad de Tunja (2023)
The main objective of this research study was to correlate the variables emotional intelligence and work environment in collaborators of a company that sells ceramic products in the city of Tunja.